Challenges of Women Agricultural Laborers in the Northern Part of Bangladesh - SEFAT-E-ZERIN, MOSAMMAD (Advances in Social Sciences Research Journal, 2019)
Still now agriculture is the biggest source of employment in Bangladesh. It provides employment for 63 percent of the population. Not only men, but also women are a big part in this sector. But in the system of male-dominated society, women have always been deprived of social barriers and discrimination. The objectives of this study is to find out what kind of work related problems the women agricultural laborers have to face. and also to identify and discuss about some factors impacting on women’s wage rate in the survey area. This survey has been conducted in 14 villages from 3 districts which are situated in the northern part in Bangladesh by questionnaire method in 2018 Total 300 respondents have been interviewed during the survey time. After getting data, it has analyzed statistically by using STATA software. The results states, women get into many problems while getting work and going to work. There is significant inequality between men and women in terms of wages. They are being deprived of their fair wage rate even though they do the same work as men. The working environment is not also in their favor. At work, they are often mistreated by their male colleagues or even by the landlords which is considered as a barrier to take participation in their work.